Scaling of a retail network in the meat processing business without loss of product quality control - Demerdzhy, Serhii (Актуальні питання економічних наук, 2026)
The relevance of the study is determined by the intensification of retail network scaling processes in the meat processing industry, which is accompanied by increasing risks of losing controllability over product quality, growing complexity of logistics flows, and higher requirements for food safety and stability of consumer characteristics. Under such conditions, traditional approaches to quality control prove to be insufficient, which necessitates the search for integrated management solutions. The purpose of the study is to substantiate effective approaches to scaling retail networks in the meat processing industry while ensuring stable product quality control. Methods. The study employs general scientific and special research methods, including analysis and synthesis to generalize approaches to quality management, systematization to structure the factors influencing scaling, comparative analysis to assess changes in the effectiveness of quality control, and logical generalization to develop practical recommendations. Results. The impact of retail network scaling on the transformation of quality control systems and the stability of product characteristics is investigated. It is found that network expansion leads to increased control dispersion, information asymmetry, and logistical risks, resulting in variability of product quality. It is proven that the effectiveness of quality management is determined by the level of process integration, digitalization, and the system’s ability to respond promptly to deviations. The feasibility of implementing multi-level models of quality control integration, combining centralized standards, local adaptation, and data-driven management, is substantiated. Conclusions. It is established that improving the effectiveness of quality management under scaling conditions is achieved through the development of a unified digital traceability framework, the advancement of preventive control, optimization of logistics processes, and the integration of quality indicators into enterprise management systems. Prospects for further research are associated with the development of methodological approaches to the quantitative assessment of the effectiveness of quality control systems, the improvement of deviation prediction models, and the study of the impact of digitalization on ensuring the stability of product characteristics in the context of retail network scaling.